Productive analysis of the supplementation with corn silage in double-purpose livestock systems - Pozo-Leyva, Dixan; Chay-Canul, Alfonso; López-González, Felipe; Cruz-Tamayo, Alvar A.; Piñeiro-Vázquez, Ángel; Casanova-Lugo, Fernando (Ecosistemas y Recursos Agropecuarios, 2022)
The deﬁcit of tropical forages in the dry season requires alterna- tive feeding strategies that involve technology transfer and the conservation of local foods. The objective was to evaluate the animal response and the cost of beneﬁt to mixed rations with different levels of inclusion of corn silage in dual-purpose production systems in southern Quintana Roo. Nine lactating cows with 152 days in milk were used in a 3 x 3 Latin square experimental design in triplicate. The treatment sequences were randomly assigned with experimental periods of 12 days, treatment one (T1) consisted of the inclusion of 15% of corn silage; T2 by 31%, T3 by 45%. Milk production, live weight, body condition, chemical composition of milk and economic viability were evaluated. Average milk production was 4.4 kg/cow−1/day−1, with a fat content of 3.3% and crude protein of 3.4%. The average live weight was 424.6 kg and the body condition of 2.3, remaining constant throughout the experiment. Differences (P < 0.05) were only observed for body condition, being favourable for T3. The incorporation of corn silage in 15, 31 or 45% cow−1 day−1 in the mixed rations of dual-purpose cows that produce 4.4 kg milk−1 day−1 did not increase milk production, but it did they have an effect on total feed costs.